Nanodomain Swelling Block Copolymer Lithography for Morphology Tunable Metal Nanopatterning. Issue 18 (13th May 2014) - Mun, Jeong Ho; Cha, Seung Keun; Kim, Hyowook; Moon, Hyoung‐Seok; Kim, Ju Young; Jin, Hyeong Min; Choi, Young Joo; Baek, Jeong Eun; Shin, Jonghwa; Kim, Sang Ouk
<x xml:space="preserve">Abstract</x> Ordered metal nanopatterns are crucial requirements for electronics, magnetics, catalysts, photonics, and so on. Despite considerable progress in the synthetic route to metal nanostructures, highly ordered metal nanopatterning over a large‐area is still challenging. Nanodomain swelling block copolymer lithography is presented as a general route to the systematic morphology tuning of metal nanopatterns from amphiphilic diblock copolymer self‐assembly. Selective swelling of hydrophilic nanocylinder domains in amphiphilic block copolymer films during metal precursor loading and subsequent oxygen based etching generates diverse shapes of metal nanopatterns, including hexagonal nanoring array and hexagonal nanomesh and double line array in addition to common nanodot and nanowire arrays. Solvent annealing condition of block copolymer templates, selective swelling of hydrophilic cylinder nanodomains, block copolymer template thickness, and oxygen based etching methods are the decisive parameters for systematic morphology evolution. The plasmonic properties of ordered Au nanopatterns are characterized and analyzed with finite differential time domain calculation. This approach offers unprecedented opportunity for diverse metal nanopatterns from commonly used diblock copolymer self‐assembly.